Influence of Current Rate on the Degradation Behavior of Lithium-Ion Battery under Overcharge Condition. Issue 12 (6th August 2019) - Ouyang, Dongxu; Weng, Jingwen; Liu, Jiahao; Chen, Mingyi; Wang, Jian
Abstract : In the present work, an experimental study is carried out to investigate the influence of current rate, i.e. cycle rate, charge rate and discharge rate on the degradation behavior of a lithium-ion battery during overcharge process. Several parameters, such as capacity degradation rate, temperature rise, temperature difference and voltage are discussed correspondingly. It is found that battery capacity experiences significant degradation under the abusive condition of overcharge cycle, and the current rate is revealed to affect the degradation rate greatly. Among, the cycle rate is exhibited to have the largest influence on the degradation of overcharged battery, followed by the charge rate and discharge rate. Under the condition of low cycle rate or low charge rate, the capacity degradation behaves much more severely, which is contrary to that of discharge condition where when decreasing the discharge rate, the degradation of battery is restrained. After the overcharge test, a recovery of discharge capacity can be observed as a function of rest time. Finally, the variation of battery internal characterizations, including the anode and separator before and after overcharge cycle are researched respectively.